A practical approach to, diagnosis, assessment and management of idiopathic intracranial hypertension. Issue 6 (8th May 2014) - Mollan, Susan P; Markey, Keira A; Benzimra, James D; Jacks, Andrew; Matthews, Tim D; Burdon, Michael A; Sinclair, Alex J
Abstract : Adult patients who present with papilloedema and symptoms of raised intracranial pressure need urgent multidisciplinary assessment including neuroimaging, to exclude life-threatening causes. Where there is no apparent underlying cause for the raised intracranial pressure, patients are considered to have idiopathic intracranial hypertension (IIH). The incidence of IIH is increasing in line with the global epidemic of obesity. There are controversial issues in its diagnosis and management. This paper gives a practical approach to assessing patients with papilloedema, its investigation and the subsequent management of patients with IIH.